Method for preparing w-ti micro-laminate composite material

CN117696892BActive Publication Date: 2026-09-29XIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311848043.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2026-09-29
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

[0004]本发明的目的是提供W-Ti微叠层复合材料的制备方法,解决了W和Ti两种金属物性差异大,制备过程中难以同时片状化的问题

Benefits of technology

[0026](1)本发明W-Ti微叠层复合材料的制备方法,基于难熔金属W高熔点、高硬度、高强度、良好的耐高温性能以及低膨胀系数等物理特性以及金属Ti密度低、韧性好等优势,将W与Ti结合在保证其高硬度、高强度的同时,可以有效提高W的韧性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117696892B_ABST
    Figure CN117696892B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of W-Ti micro-laminated composite material, and is specifically implemented according to the following steps: step 1, high-energy ball milling is performed on W powder to realize sheet layering of the W powder, and flaky W powder is obtained; step 2, the flaky W powder, TiH2 powder and molten salt are mixed to obtain mixed raw materials; step 3, the mixed raw materials are placed into an alumina magnetic boat, nitrogen gas is introduced as a protective gas in a tube furnace, deposition is performed, cooling is performed, and the molten salt is removed through repeated filtration and washing with deionized water; after freeze-drying, Ti-coated flaky W powder is obtained; and step 4, the Ti-coated flaky W powder is self-assembled through vacuum hot-pressing sintering to obtain W-Ti micro-laminated composite material. The preparation method solves the problem that W and Ti are difficult to be sheeted simultaneously due to the large difference in physical properties of the two metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite material technology, specifically relating to a method for preparing W-Ti micro-layered composite materials. Background Technology

[0002] The rapid development of modern industry has placed increasingly stringent demands on metal structural materials. Traditional materials struggle to meet the combined requirements of two or more specific properties, such as high strength, high toughness, low density, high operating temperature, corrosion resistance, and wear resistance. To meet the needs of different application fields, new metal matrix composite systems are constantly emerging, significantly improving the performance of metal structural materials. Layered metal matrix composites, through the layered composite of multiphase metals, fully leverage the intrinsic properties of different metal components and the coordinated deformation advantages between metal layers. This allows for the design of various novel materials capable of meeting complex and demanding service conditions, making it a research hotspot in recent years, especially for its unique advantages in improving the mechanical properties of composite materials. Microlaminated composites are ultra-fine layered structures prepared through biomimetic design based on the multilayered structure of nacre in natural shells. They are formed by overlapping two or more materials with different physical and chemical properties at specific interlayer spacing and thickness ratios. Their structure differs from gradient materials, with distinct interfaces between layers. Due to their multi-interface effect and small interlayer spacing, they exhibit significant performance advantages compared to monolithic materials.

[0003] Refractory metal tungsten (W) possesses high melting point, high density, high hardness, high strength, good high-temperature resistance, and low coefficient of thermal expansion, making it widely used in aerospace, military, and advanced manufacturing industries. However, due to its body-centered cubic crystal structure and limited slip systems, tungsten exhibits intrinsic brittleness and recrystallization brittleness, significantly limiting its application in extreme service environments. For tungsten materials with intrinsic brittleness, layered toughening can improve their toughness, thus tungsten-based layered composite materials have attracted increasing attention and research. Titanium (Ti), due to its low density, good ductility, and ability to form a limited solid solution with tungsten, can be used as a toughening layer for tungsten-based layered materials. However, the significant differences in the physical properties of the two metals make simultaneous lamination during the preparation process difficult. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing W-Ti micro-layered composite materials, which solves the problem that W and Ti have large differences in physical properties and are difficult to simultaneously form into sheets during the preparation process.

[0005] The technical solution adopted in this invention is a method for preparing W-Ti micro-layered composite materials, which is implemented according to the following steps:

[0006] Step 1: High-energy ball milling is performed on W powder to achieve W powder lamination, resulting in flake-shaped W powder;

[0007] Step 2: Mix the flake W powder, TiH2 powder and molten salt to obtain a mixed raw material;

[0008] Step 3: After the mixed raw materials are placed in an alumina magnetic boat, nitrogen gas is introduced into a tube furnace as a protective gas for deposition, cooling, and then repeatedly filtered and washed with deionized water to remove molten salt. After freeze-drying, Ti-coated flake W powder is obtained.

[0009] Step 4: Ti-coated flake W powder is self-assembled by vacuum hot pressing sintering to obtain W-Ti micro-laminated composite material.

[0010] The invention is further characterized in that,

[0011] The specific process of step 1 is as follows: W powder, zirconium dioxide grinding balls and anhydrous ethanol are added to a planetary high-energy ball mill and stirred. Before ball milling, the nylon ball mill jar is evacuated and filled with argon gas in sequence. After repeating this process three times, ball milling is started to obtain flake W powder.

[0012] The particle size of W powder is 1μm to 20μm;

[0013] Zirconia grinding balls are used in combination with different diameters. The diameters of the zirconia grinding balls are 8mm, 5mm and 3mm, and the ratio of large, medium and small diameter zirconia grinding balls is 3:4:5.

[0014] The mass ratio of W powder to zirconium dioxide grinding balls is 1:20;

[0015] Anhydrous ethanol accounts for 3% of the total mass of W powder and zirconium dioxide grinding balls.

[0016] The planetary high-energy ball mill has a rotation speed of 400 r / min to 800 r / min and a ball milling time of 4 h to 8 h.

[0017] The diameter / thickness ratio of the flake W powder is greater than 50.

[0018] In step 2, the molten salt is obtained by mixing and grinding KCl, NaCl and CaCl2, with a molar ratio of 1-2:1-2:1-2.

[0019] In step 2, the mass percentage of TiH2 powder is 5% to 20%, the mass percentage of flake W powder is 80% to 95%, and the sum of the mass percentages of the two is 100%.

[0020] The ratio of flake W powder to molten salt is 1:1 to 3;

[0021] The TiH2 powder has a particle size of 1μm to 30μm.

[0022] In step 3, the deposition temperature is 950℃~1250℃, the deposition time is 1h~4h, and the deposition heating rate is 10℃ / min.

[0023] The specific process of step 4 is as follows: the Ti-coated flake W powder obtained in step 3 is poured into the mold in batches. After each addition of Ti-coated flake W powder, the outside of the mold is tapped multiple times. Then, self-assembly is carried out by vacuum hot pressing sintering. During the hot pressing sintering process, a vacuum state must be maintained and the mixture is cooled with the furnace to obtain W-Ti micro-layer composite material.

[0024] The hot-pressing sintering temperature is 1250℃~1550℃, the heating rate is 100℃ / min, the holding time is 20min~60min, and the vacuum degree is less than 10. -1 Pa, with a pressing pressure of 30MPa to 60MPa.

[0025] The beneficial effects of this invention are:

[0026] (1) The preparation method of W-Ti micro-layer composite material of the present invention is based on the physical properties of refractory metal W such as high melting point, high hardness, high strength, good high temperature resistance and low expansion coefficient, and the advantages of metal Ti such as low density and good toughness. By combining W and Ti, the toughness of W can be effectively improved while ensuring its high hardness and high strength.

[0027] (2) The preparation method of W-Ti micro-layered composite material of the present invention utilizes the material structure design concept of alternating soft-hard phases of the imitation shell nacre layer to prepare biomimetic micro-layered W-Ti composite material. The multi-interface configuration design of the layered structure improves the impact toughness of the material. At the same time, the invention proposes the idea of ​​preparing W-Ti composite powder by constructing Ti-coated flake W powder by molten salt method, which effectively solves the technical difficulty of preparing W and Ti composite powders with large differences in physical properties and difficulty in simultaneously forming flakes. Attached Figure Description

[0028] Figure 1 This is a flowchart of the preparation method of the W-Ti micro-layered composite material of the present invention;

[0029] Figure 2 This is a microstructure diagram of the W-Ti microlayered composite material prepared by the method of the present invention. Detailed Implementation

[0030] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.

[0031] The preparation method of the W-Ti micro-layered composite material of the present invention, as follows: Figure 1 As shown, please follow these steps:

[0032] Step 1: High-energy ball milling is performed on W powder to achieve W powder lamination, resulting in flake-shaped W powder;

[0033] The specific process is as follows: W powder, zirconium dioxide grinding balls and anhydrous ethanol are added to a planetary high-energy ball mill and stirred. Before ball milling, the nylon ball mill jar is evacuated and filled with argon gas in sequence. After repeating this process three times, ball milling begins. The rotation speed of the planetary high-energy ball mill is 400 r / min to 800 r / min, and the ball milling time is 4 h to 8 h, to obtain flake W powder with a diameter / thickness ratio greater than 50.

[0034] Among them, the particle size of W powder is 1μm~20μm;

[0035] Zirconia grinding balls are used in combination with different diameters. The diameters of the zirconia grinding balls are 8mm, 5mm and 3mm, and the ratio of large, medium and small diameter zirconia grinding balls is 3:4:5.

[0036] The mass ratio of W powder to zirconium dioxide grinding balls is 1:20;

[0037] Anhydrous ethanol accounts for 3% of the total mass of W powder and zirconium dioxide grinding balls;

[0038] Step 2: Mix the flake W powder, TiH2 powder and molten salt to obtain a mixed raw material;

[0039] Molten salt is obtained by mixing and grinding KCl, NaCl and CaCl2, with a molar ratio of 1-2:1-2:1-2.

[0040] The mass percentage of TiH2 powder is 5%–20%, and the mass percentage of flake W powder is 80%–95%, with the sum of the two mass percentages being 100%.

[0041] The ratio of flake W powder to molten salt is 1:1 to 3;

[0042] The particle size of TiH2 powder is 1μm to 30μm;

[0043] Step 3: After the mixed raw materials are placed in an alumina magnetic boat, nitrogen gas is introduced into a tube furnace as a protective gas for deposition, cooling, and then repeatedly filtered and washed with deionized water to remove molten salt. After freeze-drying, Ti-coated flake W powder is obtained.

[0044] The deposition temperature was 950℃~1250℃, the deposition time was 1h~4h, and the deposition heating rate was 10℃ / min.

[0045] Step 4: Ti-coated flake W powder is self-assembled by vacuum hot pressing sintering to obtain W-Ti micro-laminated composite material;

[0046] The specific process is as follows: the Ti-coated flake W powder obtained in step 3 is poured into the mold in batches. After each addition of Ti-coated flake W powder, the outside of the mold is tapped multiple times. Then, self-assembly is carried out by vacuum hot pressing sintering. During the hot pressing sintering process, a vacuum state must be maintained. The mold is cooled with the furnace to obtain W-Ti micro-layer composite material.

[0047] The hot-pressing sintering temperature is 1250℃~1550℃, the heating rate is 100℃ / min, the holding time is 20min~60min, and the vacuum degree is less than 10. -1 Pa, with a pressing pressure of 30MPa to 60MPa.

[0048] Example 1

[0049] The preparation method of the W-Ti micro-layered composite material of the present invention, as follows: Figure 1 As shown, please follow these steps:

[0050] Step 1: High-energy ball milling is performed on W powder to achieve W powder lamination, resulting in flake-shaped W powder;

[0051] The specific process is as follows: W powder, zirconium dioxide grinding balls and anhydrous ethanol are added to a planetary high-energy ball mill and stirred. Before ball milling, the nylon ball mill jar is evacuated and filled with argon gas in sequence. After repeating this process three times, ball milling begins. The rotation speed of the planetary high-energy ball mill is 400 r / min and the ball milling time is 8 h to obtain flake W powder with a diameter / thickness ratio greater than 50.

[0052] Among them, the particle size of W powder is 10μm;

[0053] Zirconia grinding balls are used in combination with different diameters. The diameters of the zirconia grinding balls are 8mm, 5mm and 3mm, and the ratio of large, medium and small diameter zirconia grinding balls is 3:4:5.

[0054] The mass ratio of W powder to zirconium dioxide grinding balls is 1:20;

[0055] Anhydrous ethanol accounts for 3% of the total mass of W powder and zirconium dioxide grinding balls;

[0056] Step 2: Mix the flake W powder, TiH2 powder and molten salt to obtain a mixed raw material;

[0057] The molten salt was obtained by grinding a mixture of KCl, NaCl and CaCl2, with a molar ratio of 1:1:1.

[0058] The mass percentage of TiH2 powder is 10%, and the mass percentage of flake W powder is 90%.

[0059] The ratio of flake W powder to molten salt is 1:1;

[0060] The TiH2 powder has a particle size of 30μm;

[0061] Step 3: After the mixed raw materials are placed in an alumina magnetic boat, nitrogen gas is introduced into a tube furnace as a protective gas for deposition, cooling, and then repeatedly filtered and washed with deionized water to remove molten salt. After freeze-drying, Ti-coated flake W powder is obtained.

[0062] The deposition temperature was 950℃, the deposition time was 1h, and the deposition heating rate was 10℃ / min.

[0063] Step 4: Ti-coated flake W powder is self-assembled by vacuum hot pressing sintering to obtain W-Ti micro-laminated composite material;

[0064] The specific process is as follows: the Ti-coated flake W powder obtained in step 3 is poured into the mold in batches. After each addition of Ti-coated flake W powder, the outside of the mold is tapped multiple times. Then, self-assembly is carried out by vacuum hot pressing sintering. During the hot pressing sintering process, a vacuum state must be maintained. The mold is cooled with the furnace to obtain W-Ti micro-layer composite material.

[0065] The hot pressing sintering temperature was 1250℃, the heating rate was 100℃ / min, the holding time was 20min, and the vacuum degree was less than 10. -1 Pa, the pressing pressure is 30 MPa.

[0066] Depend on Figure 2 It is known that by constructing Ti-coated flake W powder using the molten salt method and then combining W and Ti through pressing and sintering, a micro-layered W-Ti composite material can be obtained. By designing the micro-layered structure, when subjected to load impact, the crack deflects multiple times between the layers during the fracture process, increasing the crack propagation path and thus greatly increasing the energy required for crack propagation. This consumes more impact energy, giving the material excellent strength and toughness matching properties and improving its impact resistance.

[0067] Example 2

[0068] The preparation method of the W-Ti micro-layered composite material of the present invention, as follows: Figure 1 As shown, please follow these steps:

[0069] Step 1: High-energy ball milling is performed on W powder to achieve W powder lamination, resulting in flake-shaped W powder;

[0070] The specific process is as follows: W powder, zirconium dioxide grinding balls and anhydrous ethanol are added to a planetary high-energy ball mill and stirred. Before ball milling, the nylon ball mill jar is evacuated and filled with argon gas in sequence. After repeating this process three times, ball milling begins. The rotation speed of the planetary high-energy ball mill is 400 r / min and the ball milling time is 8 h to obtain flake W powder with a diameter / thickness ratio greater than 50.

[0071] Among them, the particle size of W powder is 15μm;

[0072] Zirconia grinding balls are used in combination with different diameters. The diameters of the zirconia grinding balls are 8mm, 5mm and 3mm, and the ratio of large, medium and small diameter zirconia grinding balls is 3:4:5.

[0073] The mass ratio of W powder to zirconium dioxide grinding balls is 1:20;

[0074] Anhydrous ethanol accounts for 3% of the total mass of W powder and zirconium dioxide grinding balls;

[0075] Step 2: Mix the flake W powder, TiH2 powder and molten salt to obtain a mixed raw material;

[0076] The molten salt was obtained by grinding a mixture of KCl, NaCl and CaCl2, with a molar ratio of 2:1:1.

[0077] The mass percentage of TiH2 powder is 20%, the mass percentage of flake W powder is 80%, and the ratio of flake W powder to molten salt is 1:2.

[0078] The TiH2 powder has a particle size of 30μm;

[0079] Step 3: After the mixed raw materials are placed in an alumina magnetic boat, nitrogen gas is introduced into a tube furnace as a protective gas for deposition, cooling, and then repeatedly filtered and washed with deionized water to remove molten salt. After freeze-drying, Ti-coated flake W powder is obtained.

[0080] The deposition temperature was 950℃, the deposition time was 3 hours, and the deposition heating rate was 10℃ / min.

[0081] Step 4: Ti-coated flake W powder is self-assembled by vacuum hot pressing sintering to obtain W-Ti micro-laminated composite material;

[0082] The specific process is as follows: the Ti-coated flake W powder obtained in step 3 is poured into the mold in batches. After each addition of Ti-coated flake W powder, the outside of the mold is tapped multiple times. Then, self-assembly is carried out by vacuum hot pressing sintering. During the hot pressing sintering process, a vacuum state must be maintained. The mold is cooled with the furnace to obtain W-Ti micro-layer composite material.

[0083] The hot pressing sintering temperature was 1300℃, the heating rate was 100℃ / min, the holding time was 40min, and the vacuum degree was less than 10. -1 Pa, the pressing pressure is 30 MPa.

[0084] Example 3

[0085] The preparation method of the W-Ti micro-layered composite material of the present invention, as follows: Figure 1As shown, please follow these steps:

[0086] Step 1: High-energy ball milling is performed on W powder to achieve W powder lamination, resulting in flake-shaped W powder;

[0087] The specific process is as follows: W powder, zirconium dioxide grinding balls and anhydrous ethanol are added to a planetary high-energy ball mill and stirred. Before ball milling, the nylon ball mill jar is evacuated and filled with argon gas in sequence. After repeating this process three times, ball milling begins. The rotation speed of the planetary high-energy ball mill is 400 r / min and the ball milling time is 8 h to obtain flake W powder with a diameter / thickness ratio greater than 50.

[0088] Among them, the particle size of W powder is 20μm;

[0089] Zirconia grinding balls are used in combination with different diameters. The diameters of the zirconia grinding balls are 8mm, 5mm and 3mm, and the ratio of large, medium and small diameter zirconia grinding balls is 3:4:5.

[0090] The mass ratio of W powder to zirconium dioxide grinding balls is 1:20;

[0091] Anhydrous ethanol accounts for 3% of the total mass of W powder and zirconium dioxide grinding balls;

[0092] Step 2: Mix the flake W powder, TiH2 powder and molten salt to obtain a mixed raw material;

[0093] The molten salt was obtained by grinding a mixture of KCl, NaCl and CaCl2, with a molar ratio of 2:2:1.

[0094] The mass percentage of TiH2 powder is 10%, the mass percentage of flake W powder is 90%, and the ratio of flake W powder to molten salt is 1:2.5.

[0095] The TiH2 powder has a particle size of 1μm;

[0096] Step 3: After the mixed raw materials are placed in an alumina magnetic boat, nitrogen gas is introduced into a tube furnace as a protective gas for deposition, cooling, and then repeatedly filtered and washed with deionized water to remove molten salt. After freeze-drying, Ti-coated flake W powder is obtained.

[0097] The deposition temperature was 950℃, the deposition time was 4 hours, and the deposition heating rate was 10℃ / min.

[0098] Step 4: Ti-coated flake W powder is self-assembled by vacuum hot pressing sintering to obtain W-Ti micro-laminated composite material;

[0099] The specific process is as follows: the Ti-coated flake W powder obtained in step 3 is poured into the mold in batches. After each addition of Ti-coated flake W powder, the outside of the mold is tapped multiple times. Then, self-assembly is carried out by vacuum hot pressing sintering. During the hot pressing sintering process, a vacuum state must be maintained. The mold is cooled with the furnace to obtain W-Ti micro-layer composite material.

[0100] The hot-pressing sintering temperature was 1350℃, the heating rate was 100℃ / min, the holding time was 40min, and the vacuum degree was less than 10. -1 Pa, the pressing pressure is 30 MPa.

[0101] Example 4

[0102] The preparation method of the W-Ti micro-layered composite material of the present invention, as follows: Figure 1 As shown, please follow these steps:

[0103] Step 1: High-energy ball milling is performed on W powder to achieve W powder lamination, resulting in flake-shaped W powder;

[0104] The specific process is as follows: W powder, zirconium dioxide grinding balls and anhydrous ethanol are added to a planetary high-energy ball mill and stirred. Before ball milling, the nylon ball mill jar is evacuated and filled with argon gas in sequence. After repeating this process three times, ball milling begins. The rotation speed of the planetary high-energy ball mill is 400 r / min and the ball milling time is 8 h to obtain flake W powder with a diameter / thickness ratio greater than 50.

[0105] Among them, the particle size of W powder is 10μm;

[0106] Zirconia grinding balls are used in combination with different diameters. The diameters of the zirconia grinding balls are 8mm, 5mm and 3mm, and the ratio of large, medium and small diameter zirconia grinding balls is 3:4:5.

[0107] The mass ratio of W powder to zirconium dioxide grinding balls is 1:20;

[0108] Anhydrous ethanol accounts for 3% of the total mass of W powder and zirconium dioxide grinding balls;

[0109] Step 2: Mix the flake W powder, TiH2 powder and molten salt to obtain a mixed raw material;

[0110] The molten salt was obtained by grinding a mixture of KCl, NaCl and CaCl2, with a molar ratio of 2:2:1.

[0111] The mass percentage of TiH2 powder is 20%, the mass percentage of flake W powder is 80%, and the ratio of flake W powder to molten salt is 1:3.

[0112] The TiH2 powder has a particle size of 30μm;

[0113] Step 3: After the mixed raw materials are placed in an alumina magnetic boat, nitrogen gas is introduced into a tube furnace as a protective gas for deposition, cooling, and then repeatedly filtered and washed with deionized water to remove molten salt. After freeze-drying, Ti-coated flake W powder is obtained.

[0114] The deposition temperature was 1050℃, the deposition time was 4h, and the deposition heating rate was 10℃ / min.

[0115] Step 4: Ti-coated flake W powder is self-assembled by vacuum hot pressing sintering to obtain W-Ti micro-laminated composite material;

[0116] The specific process is as follows: the Ti-coated flake W powder obtained in step 3 is poured into the mold in batches. After each addition of Ti-coated flake W powder, the outside of the mold is tapped multiple times. Then, self-assembly is carried out by vacuum hot pressing sintering. During the hot pressing sintering process, a vacuum state must be maintained. The mold is cooled with the furnace to obtain W-Ti micro-layer composite material.

[0117] The hot-pressing sintering temperature was 1550℃, the heating rate was 100℃ / min, the holding time was 60min, and the vacuum degree was less than 10. -1 Pa, the pressing pressure is 50 MPa.

[0118] Example 5

[0119] The preparation method of the W-Ti micro-layered composite material of the present invention, as follows: Figure 1 As shown, please follow these steps:

[0120] Step 1: High-energy ball milling is performed on W powder to achieve W powder lamination, resulting in flake-shaped W powder;

[0121] The specific process is as follows: W powder, zirconium dioxide grinding balls and anhydrous ethanol are added to a planetary high-energy ball mill and stirred. Before ball milling, the nylon ball mill jar is evacuated and filled with argon gas in sequence. After repeating this process three times, ball milling begins. The rotation speed of the planetary high-energy ball mill is 800 r / min and the ball milling time is 4 h to obtain flake W powder with a diameter / thickness ratio greater than 50.

[0122] Among them, the particle size of W powder is 1μm;

[0123] Zirconia grinding balls are used in combination with different diameters. The diameters of the zirconia grinding balls are 8mm, 5mm and 3mm, and the ratio of large, medium and small diameter zirconia grinding balls is 3:4:5.

[0124] The mass ratio of W powder to zirconium dioxide grinding balls is 1:20;

[0125] Anhydrous ethanol accounts for 3% of the total mass of W powder and zirconium dioxide grinding balls;

[0126] Step 2: Mix the flake W powder, TiH2 powder and molten salt to obtain a mixed raw material;

[0127] The molten salt was obtained by grinding a mixture of KCl, NaCl and CaCl2, with a molar ratio of 2:1:2.

[0128] The mass percentage of TiH2 powder is 5%, the mass percentage of flake W powder is 95%, and the ratio of flake W powder to molten salt is 1:1.

[0129] The TiH2 powder has a particle size of 20μm;

[0130] Step 3: After the mixed raw materials are placed in an alumina magnetic boat, nitrogen gas is introduced into a tube furnace as a protective gas for deposition, cooling, and then repeatedly filtered and washed with deionized water to remove molten salt. After freeze-drying, Ti-coated flake W powder is obtained.

[0131] The deposition temperature was 1250℃, the deposition time was 1h, and the deposition heating rate was 10℃ / min.

[0132] Step 4: Ti-coated flake W powder is self-assembled by vacuum hot pressing sintering to obtain W-Ti micro-laminated composite material;

[0133] The specific process is as follows: the Ti-coated flake W powder obtained in step 3 is poured into the mold in batches. After each addition of Ti-coated flake W powder, the outside of the mold is tapped multiple times. Then, self-assembly is carried out by vacuum hot pressing sintering. During the hot pressing sintering process, a vacuum state must be maintained. The mold is cooled with the furnace to obtain W-Ti micro-layer composite material.

[0134] The hot pressing sintering temperature was 1250℃, the heating rate was 100℃ / min, the holding time was 20min, and the vacuum degree was less than 10. -1 Pa, the pressing pressure is 60 MPa.

Claims

1. A method for preparing W-Ti micro-layered composite materials, characterized in that, The specific steps are as follows: Step 1: High-energy ball milling is performed on W powder to achieve W powder lamination, resulting in flake-shaped W powder; Step 2: Mix the flake W powder, TiH2 powder and molten salt to obtain a mixed raw material; In step 2, the molten salt is obtained by mixing and grinding KCl, NaCl and CaCl2, with a molar ratio of KCl, NaCl and CaCl2 of 1~2:1~2:1~2; Step 3: After the mixed raw materials are placed in an alumina magnetic boat, nitrogen gas is introduced into a tube furnace as a protective gas for deposition, cooling, and then repeatedly filtered and washed with deionized water to remove molten salt. After freeze-drying, Ti-coated flake W powder is obtained. In step 3, the deposition temperature is 950℃~1250℃, the deposition time is 1h~4h, and the deposition heating rate is 10℃ / min; Step 4: Ti-coated flake W powder is self-assembled by vacuum hot pressing sintering to obtain W-Ti micro-laminated composite material; The specific process of step 4 is as follows: the Ti-coated flake W powder obtained in step 3 is poured into the mold in batches. After each addition of Ti-coated flake W powder, the outside of the mold is tapped multiple times. Then, self-assembly is carried out by vacuum hot pressing sintering. During the hot pressing sintering process, a vacuum state must be maintained and the mixture is cooled with the furnace to obtain W-Ti micro-layer composite material.

2. The method for preparing the W-Ti micro-layered composite material according to claim 1, characterized in that, The specific process of step 1 is as follows: W powder, zirconium dioxide grinding balls and anhydrous ethanol are added to a planetary high-energy ball mill and stirred. Before ball milling, the nylon ball mill jar is evacuated and filled with argon gas in sequence. After repeating this process three times, ball milling is started to obtain flake W powder.

3. The method for preparing the W-Ti micro-layered composite material according to claim 2, characterized in that, The particle size of W powder is 1μm~20μm; Zirconia grinding balls are used in combination with different diameters. The diameters of the zirconia grinding balls are 8mm, 5mm and 3mm, and the ratio of large, medium and small diameter zirconia grinding balls is 3:4:

5. The mass ratio of W powder to zirconium dioxide grinding balls is 1:20; Anhydrous ethanol accounts for 3% of the total mass of W powder and zirconium dioxide grinding balls.

4. The method for preparing the W-Ti micro-layered composite material according to claim 2, characterized in that, The planetary high-energy ball mill has a rotation speed of 400 r / min to 800 r / min and a ball milling time of 4 h to 8 h.

5. The method for preparing the W-Ti micro-layered composite material according to claim 2, characterized in that, The diameter to thickness ratio of the flake W powder is greater than 50.

6. The method for preparing the W-Ti micro-layered composite material according to claim 1, characterized in that, In step 2, the mass percentage of TiH2 powder is 5%~20%, the mass percentage of flake W powder is 80%~95%, and the sum of the mass percentages of the two is 100%. The ratio of flake W powder to molten salt is 1:1~3; The TiH2 powder has a particle size of 1μm to 30μm.

7. The method for preparing the W-Ti micro-layered composite material according to claim 1, characterized in that, The hot pressing sintering temperature is 1250℃~1550℃, the heating rate is 100℃ / min, the holding time is 20min~60min, the vacuum degree is less than 10-1Pa, and the pressing pressure is 30MPa~60MPa.

Citation Information

Patent Citations

  • Method for preparing titanium powder

    CN105350027A

  • Flaky powder micro-laminated W-based composite material and preparation method thereof

    CN112080676A